Implementation Of The Market Activity Transition Strategy From The Transit Market To The Sidoluhur Relocation Market Carried By The Sleman Regency Disperindag To Increase Traditional Market Customers - Iqbal Hidayat; Albari Albari (Citakonsultindo, 2024)
This study aims to analyze the implementation of the strategy to shift market activities from the transit market to the Sidoluhur relocation market by the Sleman Regency Industry and Trade Agency (Disperindag), and its impact on increasing the number of traditional market customers. Traditional markets in Sleman Regency experience challenges in maintaining their attractiveness to customers, especially with the presence of transit markets that often attract customers from more established traditional markets in terms of infrastructure. Therefore, the Sleman Regency Industry and Trade Agency (Disperindag) implemented a strategy to shift market activities from the transit market to the Sidoluhur relocation market to increase traditional market customers. This research uses a qualitative approach with in-depth interview techniques with various related parties. The interviews were conducted to gain an in-depth understanding of the implementation of the market activity transition strategy. The results showed that the implementation of the market activity transition strategy from the transit market to the Sidoluhur relocation market by the Sleman Regency Industry and Trade Agency has had a positive impact on increasing the number of traditional market customers. Factors contributing to this increase include better accessibility, improved service quality, and promotional support from the government. Nonetheless, there are still some challenges that need to be overcome, such as traders' adjustment to the new location and maintaining the sustainability of this strategy in the long term.